Feasibility of early multimodal interventions for elderly patients with advanced pancreatic and non‐small‐cell lung cancer. Issue 1 (18th October 2018) - Naito, Tateaki; Mitsunaga, Shuichi; Miura, Satoru; Tatematsu, Noriatsu; Inano, Toshimi; Mouri, Takako; Tsuji, Tetsuya; Higashiguchi, Takashi; Inui, Akio; Okayama, Taro; Yamaguchi, Teiko; Morikawa, Ayumu; et al.
Abstract: Background: Combinations of exercise and nutritional interventions might improve the functional prognosis for cachectic cancer patients. However, high attrition and poor compliance with interventions limit their efficacy. We aimed to test the feasibility of the early induction of new multimodal interventions specific for elderly patients with advanced cancer Nutrition and Exercise Treatment for Advanced Cancer (NEXTAC) programme. Methods: This was a multicentre prospective single‐arm study. We recruited 30 of 46 screened patients aged ≥70 years scheduled to receive first‐line chemotherapy for newly diagnosed, advanced pancreatic, or non‐small‐cell lung cancer. Physical activity was measured using pedometers/accelerometer (Lifecorder ®, Suzuken Co., Ltd., Japan). An 8 week educational intervention comprised three exercise and three nutritional sessions. The exercise interventions combined home‐based low‐intensity resistance training and counselling to promote physical activity. Nutritional interventions included standard nutritional counselling and instruction on how to manage symptoms that interfere with patient's appetite and oral intake. Supplements rich in branched‐chain amino acids (Inner Power ®, Otsuka Pharmaceutical Co., Ltd., Japan) were provided. The primary endpoint of the study was feasibility, which was defined as the proportion of patients attending ≥4 of six sessions. Secondary endpoints included compliance and safety. Results: The median patient age was 75 years (range, 70–84). Twelve patients (40%) were cachectic at baseline. Twenty‐nine patients attended ≥4 of the six planned sessions (96.7%, 95% confidence interval, 83.3 to 99.4). One patient dropped out due to deteriorating health status. The median proportion of days of compliance with supplement consumption and exercise performance were 99% and 91%, respectively. Adverse events possibly related to the NEXTAC programme were observed in five patients and included muscle pain (Grade 1 in two patients), arthralgia (Grade 1 in one patient), dyspnoea on exertion (Grade 1 in one patient), and plantar aponeurositis (Grade 1 in one patient). Conclusions: The early induction of multimodal interventions showed excellent compliance and safety in elderly patients with newly diagnosed pancreatic and non‐small‐cell lung cancer receiving concurrent chemotherapy. We are now conducting a randomized phase II study to measure the impact of these interventions on functional prognosis.